Research on the urban water resources carrying capacity by using system dynamics simulation - Xing Chen; Qin Xu; Jing Cai (Hydrology Research, 2023)
The relationship between water resources and social economy has become a restricting factor for sustainable development of cities around the world. Linhai City in eastern China has the fastest economic growing and population boom. The system dynamics model of water resources carrying capacity was established to analyze the interaction between society, economy and water resources of Linhai city. Six different modes of water resources utilization were designed. Taking total population, gross domestic product, industrial output value, tertiary industry output value, water consumption, water supply and sewage discharge as the measurement indexes, the research predicted the development status of water resources carrying capacity of Linhai City from 2015 to 2030 under different development modes. Through the simulation results, it is found that the water-saving measures can reduce the gap between water supply and demand only in the short term. In the long run, the adjustment of industrial structure can improve the water resources carrying capacity and simultaneously promote the economy. In addition, increase the water income sources as well as strengthen sewage treatment are also necessary to balance the water supply and demand. HIGHLIGHTS Establishment of the water resources carry a capacity prediction model based on the system dynamics model.; Sensitive variables selection for a coupled system of society, economy, water resources and environment.; Optimization of development modes and water resource utilization for the study area.;